Lymph Node Micrometastases in Early-Stage Cervical Cancer are Not Predictive of Survival. (July 2015) - Stany, Michael P.; Stone, Pamela J. B.; Felix, Juan C.; Amezcua, Charles A.; Groshen, Susan; Ye, Wei; Kyser, Kathy L.; Howard, Robin S.; Zahn, Chris M.; Muderspach, Laila I.; Lentz, Scott E.; Chernofsky, Mildred R.
Abstract : Although patients with early-stage cervical cancer have in general a favorable prognosis, 10% to 40% patients still recur depending on pathologic risk factors. The objective of this study was to evaluate if the presence of lymph node micrometastasis (LNmM) had an impact on patient's survival. We performed a multi-institutional retrospective review on patients with early-stage cervical cancer, with histologically negative lymph nodes, treated with radical hysterectomy and pelvic lymphadenectomy for the study period 1994 to 2004. Tissue blocks of lymph nodes from the patient's original surgery were recut and then evaluated for the presence of micrometastases. One hundred twenty-nine patients were identified who met inclusion criteria. LNmM were found in 26 patients (20%). In an average follow-up time of 70 mo, there were 11 recurrences (8.5%). Of the 11 recurrences, 2 (18%) patients had LNmM. Patients with LNmM were more likely to have received adjuvant radiation and chemotherapy. In stratified log-rank analysis, LNmM were not associated with any other high-risk clinical or pathologic variables. Survival data analysis did not demonstrate an association between the presence of LNmM and recurrence or overall survival. The presence of LNmM was not associated with an unfavorable prognosis nor was it associated with other high-risk clinical or pathologic variables predicting recurrence. Further study is warranted to understand the role of micrometastases in cervical cancer.